2015
DOI: 10.1111/rec.12313
|View full text |Cite
|
Sign up to set email alerts
|

Artificial canopy gaps accelerate restoration within an exoticPinus radiataplantation

Abstract: We created small-scale artificial canopy gaps to accelerate the growth of mature indigenous forest canopy species for restoration of an 18-year-old exotic Pinus radiata plantation forest, in the Marlborough Sounds, New Zealand. Small and large circular gaps were formed by felling. Seedlings of two indigenous forest canopy species, Podocarpus totara (Podocarpaceae) and Beilschmiedia tawa (Lauraceae), were planted within artificial gaps and undisturbed plantation canopy. Seedling height growth, mortality, and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Although some seedlings grew as tall as or taller than in the gap treatment, others did not. Survival was also lower in the edge sites, which was likely due to enhanced herbivory (most likely by feral red deer; D. Norton 2017, University of Canterbury, personal communication) which impacted some plants at these sites similar to the effect of herbivory on tōtara seedlings planted into Pinus canopy gaps (Forbes et al ). While our study did not account for this browsing damage, herbivory by introduced mammals is a common problem in New Zealand forests and has been observed to restrict establishment of many indigenous tree species across a range of light levels (Husheer et al ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some seedlings grew as tall as or taller than in the gap treatment, others did not. Survival was also lower in the edge sites, which was likely due to enhanced herbivory (most likely by feral red deer; D. Norton 2017, University of Canterbury, personal communication) which impacted some plants at these sites similar to the effect of herbivory on tōtara seedlings planted into Pinus canopy gaps (Forbes et al ). While our study did not account for this browsing damage, herbivory by introduced mammals is a common problem in New Zealand forests and has been observed to restrict establishment of many indigenous tree species across a range of light levels (Husheer et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, total light transmission under gaps was 33% of open sky conditions, similar to the 30% total light transmission under large, naturally formed, canopy gaps in dense‐mixed forest in central North Island, New Zealand, that was found to result in the best growth of tōtara seedlings in a natural setting (Ebbett & Ogden ). In a study looking at two gap sizes in an exotic Pinus radiata plantation, in central New Zealand, Forbes et al () found significantly higher tōtara growth in gaps with at least 50% light transmission, although larger canopy gaps with 84% light transmission were more favorable for planted tōtara seedlings. Similar growth response with increasing light transmittance has been reported in other gap studies (Ramos & del Amo ; Coates & Burton ; Fahey & Lorimer ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern confirms our second hypothesis that in degraded North-Patagonian forests, N. nitida planted seedlings present higher browsing rates in places with higher %PPFD and/or lower residual basal area. For both removal of the understory and reduced (degraded) tree overstory, higher browsing rates have been found for many species and forest types worldwide (H orsley et al 2003, Tremblay et al 2007, Kuijper et al 2009, Churski et al 2016, Forbes et al 2016, Charron & Hermanutz 2017, Bose et al 2018. However, this pattern has shown controversial results for different species worldwide and thus, is a widely discussed issue (C asabon & Pothier 2007, Tremblay et al 2007, Kuijper et al 2009, Gerhardt et al 2013.…”
Section: Browsing Evidence In Restoration Plantings On Chiloé Islandmentioning
confidence: 99%